The Pedagogy Inherent in Japan's Early Childhood Education Curricula by Bibliometric Analysis - Rie Takahashi; Yeni Rachmawati; Naomi Takasawa (IJECA (International Journal of Education and Curriculum Application), 2026)
The establishment of the Child and Family Agency in 2023 marked a critical turning point in Japan's early childhood education and care (ECEC) system. However, systematic empirical evidence on the pedagogical foundations of of Japanese ECEC curricula remains limited. This study employs a systematic bibliometric review aimed at exploring the structural characteristics and dominant pedagogical frameworks of ECEC curriculum under institutional transformation. In accordance with the PRISMA guidelines, a comprehensive literature review of 972 papers identified by the Publish or Perish tool with a focus on Google Scholar was conducted, encompassing publications from 2022 to 2025. The primary research instrument employed was VOSviewer, a software program designed for analysing scientific literature. This software enabled the execution of two key research methodologies: keyword co-occurrence mapping and conceptual clustering.The findings reveal that pedagogy, curriculum and children are the central pillars of the Japanese ECEC curricula. Distinct conceptual clusters emerge, including the close association between play and care, as well as patterns reflecting indirect education (Kansetsu Kyoiku). Additionally, a significant discrepancy is observed between the national curriculum and its implementation in practice. In conclusion, this study offers three key contributions. Firstly, it provides a visual taxonomy that bridges the gap between abstract national policy and actual research trends. Secondly, it identifies a significant conceptual discrepancy between the 'intended curriculum' and the 'practised curriculum', highlighting a critical area for future qualitative inquiry. Finally, it provides an empirical basis for culturally embedded educational logics, thereby offering a new theoretical framework for international comparative ECEC research.